PROGRAM PARENTING KELAS PERTEMUAN ORANG TUA (KPO) DAN KETERLIBATAN ORANG TUA DALAM KELOMPOK KELAS ANAK ( KOK ) - Regina, Putri; Puspita, Bella; Putri, Yecha Febrieanitha (HYPOTHESIS : Multidisciplinary Journal Of Social Sciences, 2022)
This article discusses the steps of the parenting program for parent meeting classes (KPO) and parental involvement in children's class groups (KOK). The purpose of this study was to find out the steps or ways to carry out parenting programs for parent meeting classes (KPO) and parental involvement in children's class groups (KOK). This study used a qualitative approach, namely to describe and describe the steps of the parenting program in the parent meeting class (KPO) and parental involvement in the child's class group (KOK). The data collection technique used in this study library research, where library research is the activity of collecting research-related materials from books, scientific journals, literature and other publications that are worthy of being used as sources. for research that will be examined by the author, by describing and describing the data through several expert opinions.